International Sourcing and Capital Structure - Eun, Cheol S.; Wang, Lingling (Review of Finance, 2016)
Abstract Motivated by the rising importance of international sourcing by US firms in recent decades, we study the influence of international sourcing on capital structure. We find that international sourcing has a significant negative influence on financial leverage. The negative influence is stronger in industries that have high R&D intensities and are financially constrained. However, the negative relation is mitigated when suppliers are from countries with strong legal environments and when the supplier markets are more competitive. Overall, our findings suggest that relationship-specific investments, supplier market characteristics, and financial market conditions are key determinants of the sourcing–leverage relation.